Creating the Moorfields' virtual eye casualty: video consultations to provide emergency teleophthalmology care during and beyond the COVID-19 pandemic. Issue 3 (13th August 2020) - Kilduff, Caroline LS; Thomas, Alice AP; Dugdill, Juliet; Casswell, Edward J; Dabrowski, Marcin; Lovegrove, Claire; Sim, Dawn A; Hay, Gordon R; Thomas, Peter BM
Abstract : Background: The COVID-19 crisis forced hospitals in the UK dramatically to reduce outpatient activity. To provide continuity of care and to assist patients reluctant or unable to leave their homes, video consultations were rapidly implemented across routine and emergency ophthalmology services. Objective: To describe the deployment and scaling to a large volume of teleophthalmology using a video consultation platform 'Attend Anywhere' in Moorfields Eye Hospital's accident and emergency (A&E) department (London, UK). Method: Patient satisfaction, waiting time, consultation duration, outcome and management were audited following the launch of the new virtual A&E service. Results: In the 12 days following the service launch, 331 patients were seen by video consultation. 78.6% of patients (n=260) were determined not to need hospital A&E review and were managed with advice (n=126), remote prescription (n=57), general practitioner referral (n=27), direct referral to hospital subspecialty services (n=26) or diversion to a local eye unit (n=24). Mean patient satisfaction was 4.9 of 5.0 (n=62). The mean consultation duration was 12 min (range 5–31 min) and the wait time was 6 min (range 0–37 min). Conclusion: Video consultations showed greater than expected usefulness in the remote management of eye disease and supported a substantial reduction in the number of people visiting the hospital.